Influence law of abnormal coal thickness zone on coal and gas outburst - Jupeng TANG; Zhonghua ZHANG; Yishan PAN; Lingran REN; Xin ZHANG; Lei HUANG (Meitan xuebao)
Coal and gas outburst is the most serious dynamic disaster threatening the safety production of coal mines in China. The abnormal area of coal thickness is an important factor affecting the occurrence of coal and gas outburst. In order to reveal the influence law of coal thickness anomaly area on coal and gas outburst, the self-developed true triaxial coal and gas outburst similar simulation test system was used to study the 14151 outburst coal seam of Xin 'an Coal Mine in Luoyang.Combined with the acoustic emission ( AE ) monitoring device, the coal thickness of 4, 5, 6, 7 m and the coal thickness change rate of 1, 2, 3, 4 m/dam coal and gas outburst similar simulation test were simulated respectively, combined with the field outburst accident. The test results of roof collapse, critical gas pressure, relative outburst strength and acoustic emission characteristic parameters were compared and analyzed. Combined with the crack propagation inside the coal body, the relationship between the abnormal area of coal thickness and the precursor information of coal and gas outburst was established. The results show that : Under the same in-situ stress conditions, the relative outburst strength of the coal thickness anomaly area is affected by the critical gas pressure and the stability of the coal seam. The relative outburst strength has a quadratic function relationship with the change rate of coal thickness. The relative outburst strength increases first and then decreases with the increase of the change rate of coal thickness, and reaches the peak at 2-3 m/dam. From the perspective of AE energy, the process of coal and gas outburst is an evolution process from low-energy stable state to high-energy unstable state, and the first critical point is proposed. When the coal thickness increases by 1 m, the first critical gas pressure decreases by 11.78%, 12.82% and 11.37%, respectively. The change rate of coal thickness increases by 1 m/dam, and the first critical gas pressure decreases by 22.14%, 17.54% and 21.49%, respectively. It shows that the thickening of coal seam and the increase of the change rate of coal thickness will lead to the earlier occurrence of the first critical point, and the change rate of coal thickness has a more significant effect on the stability of coal seam. According to the ratio of the average slope of cumulative AE energy in different stages, the quantitative indexes of weak, medium and strong risk of coal and gas outburst are defined, which can provide reference for the prevention and control of dynamic disasters of coal and gas outburst.